Brand Image Product Quality and Price Perception Drive Marina Purchase Decisions: Citra Merek, Kualitas Produk, dan Persepsi Harga Menjadi Faktor Penentu dalam Keputusan Pembelian Marina - Sembiring, Elsa Evipania Br; Ikaningtyas, Maharani (Academia Open, 2026)
General Background: The cosmetics and personal care industry in Indonesia continues to grow as consumers become more aware of skin protection and body care needs. Specific Background: In tropical urban markets, hand and body lotion purchasing decisions are shaped by consumer evaluations of brand image, product quality, and price perception amid competitive local and global brands. Knowledge Gap: Previous studies have shown inconsistent findings regarding brand image, product quality, and price perception, while integrated evidence on hand and body lotion purchasing decisions remains limited. Aims: This study aimed to analyze the partial and simultaneous relationships between brand image, product quality, price perception, and purchasing decisions for hand and body lotion consumers. Results: Using an associative quantitative design, questionnaire data from 150 respondents were analyzed through multiple linear regression with SPSS 25. Brand image, product quality, and price perception each had positive and significant relationships with purchasing decisions, with product quality showing the strongest coefficient at 0.394, followed by price perception at 0.291 and brand image at 0.269. The model showed a strong relationship with R = 0.820 and explained 67.3% of purchasing decision variance. The simultaneous test was also significant, with F = 100.035 and p = 0.000. Novelty: This study integrates three consumer perception variables in one model for hand and body lotion purchasing behavior. Implications: The findings suggest that marketers should prioritize consistent product quality, positive brand associations, and price suitability to strengthen consumer purchase decisions. Highlights: Quality assessment recorded the strongest regression coefficient. The model explained 67.3% of buyer choice variance. All three consumer perception factors were statistically significant. Keywords: Brand Image, Purchasing Decision, Product Quality, Price Perception